Antimicrobial particles from cationic lipid and polyelectrolytes - Melo, Letícia D (Langmuir : the ACS journal of surfaces and colloids, 2010)
Hybrid nanoparticles from cationic lipid and polymers were prepared and characterized regarding physical properties and antimicrobial activity. Carboxymethylcellulose (CMC) and polydiallyldimethylammonium chloride (PDDA) were sequentially added to cationic bilayer fragments (BF) prepared from ultrasonic dispersion in water of the synthetic and cationic lipid dioctadecyldimethylammonium bromide (DODAB). Particles thus obtained were characterized by dynamic light-scattering for determination of z-average diameter (Dz) and zeta-potential (zeta). Antimicrobial activity of the DODAB BF/CMC/PDDA particles against Pseudomonas aeruginosa or Staphylococcus aureus was determined by plating and CFU counting over a range of particle compositions. DODAB BF/CMC/PDDA particles exhibited sizes and zeta-potentials strictly dependent on DODAB, CMC, and PDDA concentrations. At 0.1 mM DODAB, 0.1 mg/mL CMC, and 0.1 mg/mL PDDA, small cationic particles with Dz = 100 nm and zeta = 30 mV were obtained. At 0.5 mM DODAB, 0.5 mg/mL CMC and 0.5 mg/mL PDDA, large cationic particles with Dz = 470 nm and zeta = 50 mV were obtained. Both particulates were highly reproducible regarding physical properties and yielded 0% of P. aeruginosa viability (10(7) CFU/mL) at 1 or 2 microg/mL PDDA dissolved in solution or in form of particles, respectively. 99% of S. aureus cells died at 10 microg/mL PDDA alone or in small or large DODAB BF/CMC/PDDA particles. The antimicrobial effect was dependent on the amount of positive charge on particles and independent of particle size. A high microbicide potency for PDDA over a range of nanomolar concentrations was disclosed. P. aeruginosa was more sensitive to all cationic assemblies than S. aureus